Effects of aerobic and inspiratory training on skeletal muscle microRNA‐1 and downstream‐associated pathways in patients with heart failure. Issue 1 (19th November 2019) - Antunes‐Correa, Ligia M.; Trevizan, Patricia F.; Bacurau, Aline V.N.; Ferreira‐Santos, Larissa; Gomes, João L.P.; Urias, Ursula; Oliveira, Patricia A.; Alves, Maria Janieire N.N.; de Almeida, Dirceu R.; Brum, Patricia C.; Oliveira, Edilamar M.; Hajjar, Ludhmila; et al.
Abstract: Background: The exercise intolerance in chronic heart failure with reduced ejection fraction (HFrEF) is mostly attributed to alterations in skeletal muscle. However, the mechanisms underlying the skeletal myopathy in patients with HFrEF are not completely understood. We hypothesized that (i) aerobic exercise training (AET) and inspiratory muscle training (IMT) would change skeletal muscle microRNA‐1 expression and downstream‐associated pathways in patients with HFrEF and (ii) AET and IMT would increase leg blood flow (LBF), functional capacity, and quality of life in these patients. Methods: Patients age 35 to 70 years, left ventricular ejection fraction (LVEF) ≤40%, New York Heart Association functional classes II–III, were randomized into control, IMT, and AET groups. Skeletal muscle changes were examined by vastus lateralis biopsy. LBF was measured by venous occlusion plethysmography, functional capacity by cardiopulmonary exercise test, and quality of life by Minnesota Living with Heart Failure Questionnaire. All patients were evaluated at baseline and after 4 months. Results: Thirty‐three patients finished the study protocol: control ( n = 10; LVEF = 25 ± 1%; six males), IMT ( n = 11; LVEF = 31 ± 2%; three males), and AET ( n = 12; LVEF = 26 ± 2%; seven males). AET, but not IMT, increased the expression of microRNA‐1 ( P = 0.02; percent changes = 53 ± 17%), decreased the expression of PTEN ( P = 0.003; percent changes = −15 ± 0.03%), and tended to increase the p‐AKT ser473 /AKT ratio ( P = 0.06). In addition, AET decreased HDAC4 expression ( P = 0.03; percent changes = −40 ± 19%) and upregulated follistatin ( P = 0.01; percent changes = 174 ± 58%), MEF2C ( P = 0.05; percent changes = 34 ± 15%), and MyoD expression ( P = 0.05; percent changes = 47 ± 18%). AET also increased muscle cross‐sectional area ( P = 0.01). AET and IMT increased LBF, functional capacity, and quality of life. Further analyses showed a significant correlation between percent changes in microRNA‐1 and percent changes in follistatin mRNA ( P = 0.001, rho = 0.58) and between percent changes in follistatin mRNA and percent changes in peak VO2 ( P = 0.004, rho = 0.51). Conclusions: AET upregulates microRNA‐1 levels and decreases the protein expression of PTEN, which reduces the inhibitory action on the PI3K‐AKT pathway that regulates the skeletal muscle tropism. The increased levels of microRNA‐1 also decreased HDAC4 and increased MEF2c, MyoD, and follistatin expression, improving skeletal muscle regeneration. These changes associated with the increase in muscle cross‐sectional area and LBF contribute to the attenuation in skeletal myopathy, and the improvement in functional capacity and quality of life in patients with HFrEF. IMT caused no changes in microRNA‐1 and in the downstream‐associated pathway. The increased functional capacity provoked by IMT seems to be associated with amelioration in the respiratory function instead of changes in skeletal muscle. ClinicalTrials.gov (Identifier: NCT01747395)